Medical malpractice as a separate criminal offense - Vuletić, Igor (Medicine, law & society, 2019)
A comparative overview of the criminalisation of medical errors in Europe shows that this in principle is approached in two ways. Under the first approach, such errors are incriminated through the general regime for criminal offenses, such as bodily injury or causing death by negligence. The second approach, adopted in a smaller number of countries, prescribes it as a separate criminal offense (as medical malpractice). Croatian law is a typical example of the second model, which has given rise to discussions in Croatian scholarly circles about the abandonment of such a model. The author analyses the Croatian legislative solution and its realisation in judicial practice, and based on this analysis, through the presentation of noteworthy case law, provides conclusions on whether or not the Croatian legislative solution indeed provides a higher degree of protection of the health of patients and a higher level of legal certainty.
Keywords: causal nexus; civilno pravo; doctor; gross negligence; Hrvaška; medical malpractice; medicina; odškodninska odgovornost; rules of the profession; zdravstvene napake